Caracterização molecular e estrutural de quitinases de Moniliophthora perniciosa (Stahel) Aime & Phillips-Mora - Silva, Raquel Aguiar da (2018)
Chitin is considered the second most important biopolymer in nature. The natural accumulation in the environment is incompatible with its uninterrupted production, which shows that natural mechanisms exist because of its degradation. These enzymes are found in almost all types of living beings; they are interest in biotechnology because they allow the degradation of chitin in products useful to several productive sectors of the economy, highlighted for fungal origin. In view of this scenario, a molecular characterization from RNA extraction and cDNA amplification and an analysis of 3D structures by comparative modeling of sequences from Moniliophthora perciniosa (STAHEL) AIME & PHILLIPS-MORA genome were aimed in this study. The fungus grown on WY medium for 8-10 days grew vigorously under conditions where the wheat bran was well ground. As an expression of quitinase is crucial for the fungus growth, this medium was considered satisfactory for RNA extraction. The traditional Trizol method was more favorable than the use of RNA extraction kits. For detection of M. perniciosa quitinase expression from cDNA amplification, fragments related to the specific amplification region determined by genome sequences (16426) and using primers Chit_TEIX_F / Chit_TEIX_R were found. From the 14 chitinase sequences obtained from the genome, all of them showed catalytic domain, the best of them presented 49,48% identity to template (3G6M). A statistical analysis using the RAMACHANDRAN graph showed that the best model sequence (997) had 97,2% residues in favorable regions. In 5 models were found active site, its position and the residues involved in the catalysis. The 5 models constructed from the alignment of sections 15210, 1679, 4357, 5707 and 997 with their templates by MODELLER presented a classic alpha-beta barrel structure containing α-helices and β-sheets. After sequential alignment, refinement and Molecular Dynamics, the final model (997) analyzed by SWISS MODEL presented high structural similarity with its respective mold. From the 3D models of the chitinases and the specific fragment amplified by PCR, the use of specific primers for the generated models, sequencing and cloning are objectives for later works.